Una revolución silenciosa. El impacto de la Constitución de Cádiz en el virreinato del Perú, 1812-1823 - Escanilla Huerta, Silvia (2023)
This article argues that the impact of the Constitution of Cadiz among indigenous communities in the Viceroyalty of Peru was significant. In the context of the imperial crisis of the Spanish crown, indigenous peoples took the tools that the Constitution granted them to increase their level of self-government. Moreover, the changes implemented by the Constitution persisted after its abolition, allowing indigenous peoples to retain a level of self-government otherwise impossible to conceive after Ferdinand VII restored absolutist rule. Their actions demonstrate that the Constitution was a watershed moment in the history of the Viceroyalty because it inaugurated an era of political change with consequences nobody could predict at the time.